THE INFLUENCE OF THE QUALITY OF SUSTAINABLE DEVELOPMENT GOALS DISCLOSURE, INSTITUTIONAL OWNERSHIP, AND INDEPENDENT BOARD OF COMMISSIONERS ON FIRM VALUE (A STUDY ON FINANCIAL TECHNOLOGY (FINTECH) COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2021–2023) - Malau, Yemima Christiani; Mukhzarudfa, Mukhzarudfa; Mansur, Fitrini (Penelitian dan Pengembangan Ilmu, 2025)
This study is to examine the impact of institutional ownership, the independent board of commissioners, and the quality of Sustainable Development Goals (SDGs) disclosure on business value in the Financial Technology (Fintech) industry listed on the Indonesia Stock Exchange (IDX) for the years 2021–2023. The increasing focus of investors on environmental concerns and sound corporate governance in assessing business value serves as the backdrop for this study. Purposive sampling is employed in this quantitative study design. The information was taken from the sustainability and annual reports of businesses. Multiple linear regression was used in the analysis. The findings indicate that while institutional ownership has no discernible impact on corporate value, the independent board of commissioners and the quality of SDG disclosures do have a significant effect. These findings imply that Fintech companies need to improve sustainability transparency and pay attention to ownership structure to enhance firm value in the eyes of investors.